Особливості комплексного маркетингову підходу в менеджменті туристичної індустрії - Zamlynskyi, Viktor; Yurchenko, Natalia; Haltsova, Olga (Dr. Viktor Koval, 2018)
Introduction. The tourist industry is a priority in the strategic development of a region. The main problems of research in the field of marketing tourism services are the essence and role of marketing in the development of the tourism industry, including the process of marketing management, types of strategies and marketing plans. The purpose of marketing tourism services is to attract as many customers as possible to the business entities, while providing them with the highest quality of service and guaranteeing their full satisfaction as part of the basic and expanded product. Aim and tasks. The purpose of this article is to study specifics and the complex nature of marketing in the tourism industry. Results. In the modern period of functioning of the economy, the service industry is developing very dynamically. In connection with this, the specificity of marketing used in travel services is also changing. The article analyzes the models of state regulation of the tourism industry. World practice separates the four models of state regulation of tourism industry. Eligible for the development of the tourist industry of Ukraine is the third "European" and fourth "Mixed" model, based on solid cooperation between the state and private business, i.e. the presence of central executive authority, recognition tourism is a priority area for the country. It is proved that the main positive point in introducing these models is that the State acts as the coordinator for the development of the tourism industry. The essence and features of the concept of "tourist demand" and "tourist offer" are also analyzed. Established in the tourist marketing system of continuous coordination of services in the marketing process with those that are in demand in the market, and which are planned to be introduced to the market with greater profits than competitors do. Conclusions. After analyzing the current concepts of marketing in tourism, we came to the conclusion that it is necessary to consider them through the concept of marketing interaction, that is, when using social and communication techniques to enhance marketing activities in tourism. Having reviewed the model of state regulation of tourism development, it was noted that it is European model of state participation in the development of the tourism industry is acceptable for Ukraine. It would be wise to develop a model tourism management in Ukraine and its regions that will meet the peculiarities of country and will make it possible to work effectively at this stage of development of tourism in Ukraine. With regard to public relations tools as a general form of promotion of travel services, they are quite popular among tourists. However, the state needs to pay special attention to the development of recreational areas, and other areas of tourism in Ukraine.